Clinical Evaluation of Treatment Plans for some of Foot Deformity forms in Patients with Neurological Diseases - Frolov, Vladimir A. (International Journal of Psychosocial Rehabilitation, 2020)
The rationale for the present work is in the fact that diagnostics and rehabilitation treatment for nervous and musculoskeletal systems diseases remain acute among issues of theoretical and clinical medicine. Hence, the present article describes the prospects of diagnostics and rehabilitation treatment improvement in patients with feet deformities associated with central and peripheral nervous system diseases. The study was based on clinical neurophysiological analysis.The main study methods were plantography examination and clinical-neurological and psychological testing performed for 128 patients (75 females and 53 males) with clinical picture of neurological disorders in feet. This approach allowed the authors to evaluate the recommendations on non-specific orthopedic therapy for different neurogenic feet deformities and to optimize the complex of therapeutic measures based on the results of clinical questionnaire. This approach contributes to the improvement of primarily diagnostics of feet functional disorders associated with nervous system diseases.In the present article the importance of peripheral neuromotor functional and peripheral maintaining factors insufficiency for diagnostics, disease prognosis and improvement of foot dystonia treatment efficiency is shown. The materials presented in the article are of practical value to neurologists, chiropractics, osteopathic physicians, podiatric specialists and recreation therapists that rely on complex approach in diagnostics and treatment of older patients.